(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2025)
This article provides a comprehensive analysis of the prospects and current problems of the development of the tourism sector of Uzbekistan in the context of a digital and innovative economy. The study highlights new opportunities arising in the tourism industry as a result of the introduction of digital technologies, innovative services, electronic platforms, artificial intelligence, big data and mobile applications. It also analyzes factors such as insufficient development of digital infrastructure, human resources, the level of use of information technologies, marketing and branding problems, and interregional imbalances. The article puts forward proposals and recommendations aimed at increasing the competitiveness of Uzbek tourism through digitalization, increasing the flow of tourists and improving the quality of services.